Peningkatan Motivasi Belajar Matematika Melalui Penerapan Strategi Course Review Horay pada Siswa Kelas IV SD Negeri 1 Kendel Boyolali Tahun Pelajaran 2015/2016 - Cahyani, Arisma Wahyu Putri (2016)
Arisma Wahyu Putri Cahyani /A510120078. IMPROVEMENT THROUGH THE IMPLEMENTATION OF MOTIVATION TO LEARN MATH COURSE REVIEW HORAY STRATEGY IN GRADE IV OF SD NEGERI 1 KENDEL BOYOLALI, YEAR 2015/2016. Research paper. The Faculty of Education, University of Muhammadiyah Surakarta. February, 2016. The aim of this study is to increase motivation and the student achievements on mathematics subject using course review horay strategy in grade IV SD Negeri 1 Kendel Boyolali. The kind of this research is classroom action research (PTK). The total subject recipients of the action are 27 students on fourth grade of SD Negeri 1 Kendel Boyolali. Data collection techniques are: interviews, observation, documentation, and examinations. Technique of analysis data is descriptive qualitative, data collection used are data reduction, data presentation, and conclusion. Results of the study show the improvements in students' motivation in learning mathematics. These results show that indicators of students motivation achievement improve to learn which include: 1) The learning pleasure and passion before action is 48,15%, the first cycle of the first meeting 59,26%, the first cycle of second meeting 66,67%, the second cycle of the first meeting 81,48%, the second cycle in second meeting 88,89%. 2) The courage in answering questions from the teacher before action 37,04%, the first cycle of the first meeting of 44.44%, the first cycle of second meeting 59,26%, the second cycle of the first meeting 70,37%, %, the second cycle in second meeting 81,48% , 3) The active participation of students in a group discussion before action 40,74%, the first cycle of the first meeting 51,58%, the first cycle of second meeting 62,96%, the second cycle of the first meeting 77,78%, the second cycle in second meeting 85,19%. 4) Willingness to listen to the explanation of the teacher before action 51,85%, the first cycle of the first meeting 59,26%, the first cycle of second meeting 66,67%, the second cycle the first meeting 77,78%, the second cycle in second meeting 85,19%. 5) Willingness to do exercises given by the teacher before the actions 51,85%, the first cycle of the first meeting 62,96%, the first cycle of second meeting 70,37%, the second cycle the first meeting 85,19%, the second cycle in second meeting 92,59%. Besides, the learning outcomes of students also increase. Before the action class average value of 71,11 with learning completeness of 48,14%, the first cycle of the first meeting of the average value improves 72,22 with learning completeness of 59,26%, the first cycle of the second meeting of the average value increases into 74,44 by 66,67% completeness study, the first meeting of the second cycle the average value improves to 76,30 with learning completeness of 77,78%, and the first meeting of the second cycle the average value improves to 80,37 with mastery learning amounting to 88,89%. The conclusion of this study is that the implementation of the course review horay strategy can enhance the learning motivation fourth grade students of SD Negeri 1 Kendel Boyolali in mathematics subject year 2015/2016. Keywords: Learning motivation, Course Review Horay Strategy.